Implementation and Evaluation of an Economic Model for Telestroke: Experience from Virtuall, France - Riou-Comte, Nolwenn; Mione, Gioia; Humbertjean, Lisa; Brunner, Arielle; Vezain, Arnaud; Lavandier, Karine; Marchal, Sophie; Bracard, Serge; Debouverie, Marc; Richard, Sébastien (Frontiers in Neurology, 2017)
Background. Telestroke is recognized as a safe and time-efficient way of treating stroke patients. However, admission centers (spokes) are subject to financial charges which can make them reluctant to join the system. We implemented and assessed an economic model supporting our telestroke system, Virtuall, France, which includes one expert center (hub) and six spokes. Methods. The model is based on payment for the expertise provided by the hub, distribution of charges related to telemedicine according to the fees perceived by the spokes, and transfer of patients between the spokes and the hub. We performed a cost-benefit analysis for all patients included in Virtuall from January 2014 to December 2015 to assess the economic balance in each center. Results. 321 patients were prospectively included in the study. Application of the economic model resulted in overall financial balance with funding of a dedicated medical service in the hub, and reduced costs directly related to telestroke by an average of 10% in the spokes. The conditions generating the highest costs for the spokes were: a patient returning from the hub for re-hospitalization (mean cost of $1995/patient); management of patients treated by intravenous thrombolysis without transfer to the hub (mean cost of $2075/patient). The most favorable financial condition for the spokes remained simple transfer of patients to the hub and no return (mean cost of $329/patient). Conclusion. We describe an economic model which can be applied to any telestroke system to ensure the optimal balance between hub and spoke centers.